Bioglass-polycitrate-derived luminescent carbon dots and preparation method and application thereof
By preparing the bioglass-polycitric acid complex and isolating the luminescent carbon dots, the problem of limited osteogenesis using bioactive glass alone is solved, and the dual application in osteogenesis and cell imaging is achieved, with excellent osteogenesis and photoluminescence characteristics.
Patent Information
- Application Number
- CN202410751206.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-12
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-06-12
AI Technical Summary
In the prior art, the use of bioactive glass alone has limited osteogenic effects in bone regeneration, and the application of carbon dots in the field of biomedical science has not yet fully utilized its osteogenic and photoluminescent properties.
By preparing a bioglass-polycitric acid complex and separating the luminescent carbon dots therein, the osteogenesis action is used to promote the differentiation of osteogenic precursor cells and trace cells in cell imaging by photoluminescence properties.
The bioglass-polycitric acid complex promotes osteogenesis, and the isolated luminescent carbon dots show good application potential in cell imaging, with low toxicity, good water solubility, high quantum yield and good photostability.
Smart Images

Figure CN118703206B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of luminescent and osteogenic materials, and in particular is a bioglass-polycitrate-derived luminescent carbon dot and a preparation method and application thereof. Background Art
[0002] Carbon dots (CDs) are an emerging class of carbon nanomaterials with attractive properties and promising applications in the biomedical field. CDs typically exhibit photoluminescence emission spectra that are dependent on the excitation wavelength. They also have high photostability and strong resistance to photobleaching. In vitro and in vivo cytotoxicity and biocompatibility studies have shown that CDs have no significant toxic effects. In addition, the interactions of CDs with biomacromolecules (i.e., proteins, nucleic acids, and lipids) have been extensively studied. Due to these superior properties, CDs have found significant applications in the biomedical field (i.e., bioimaging, drug delivery, and therapeutics development).
[0003] Bone tissue engineering (BTE) has attracted extensive attention due to its great potential in treating critical-sized bone defects and related diseases. As a rising star in the field of BTE, silicate bioactive glass (BG) has attracted increasing attention due to its excellent biocompatibility, bioactivity, and osteoconductivity, making it suitable for bone regeneration. Zheng et al. demonstrated that BG can stimulate bone tissue to release endogenous bioactive factors, such as vascular endothelial growth factor (VEGF), thereby inducing angiogenesis. The chances of successful bone repair are highly dependent on the vascularization of the graft. However, previous studies have confirmed that the osteogenesis of BG alone is limited.
[0004] Citric acid, as an important intermediate of the Kreb cycle, has a high concentration in natural bone (90% of the total citric acid content in the human body is located in the skeletal system) and is closely related to bone metabolism and formation. Citric acid can promote the osteogenic differentiation and matrix mineralization of MSCs (bone marrow mesenchymal stem cells) and can also be used as a precursor for the preparation of CDs. Therefore, it is of great significance to add citric acid to BG, prepare a PEC-GS / BG complex, and separate fluorescent CDs. Summary of the invention
[0005] In order to solve the above problems, the purpose of the present invention is to provide a bioglass-polycitrate-derived luminescent carbon dots and a preparation method and application thereof.
[0006] In order to achieve the above object, the present invention is implemented through the following technical solutions:
[0007] A bioglass-polycitric acid-derived luminescent carbon dot is prepared according to the following method: firstly, a bioglass-polycitric acid complex is prepared, and then the luminescent carbon dot is separated therefrom.
[0008] The preparation of the bioglass-polycitrate-derived luminescent carbon dots comprises the following steps:
[0009] 1) under nitrogen protection, polyethylene glycol and citric acid are added to a reactor, heated to 130-150° C. under stirring, reacted for 0.5-1 h to obtain a polyethylene glycol citric acid prepolymer, cooled to 25-30° C., and then methoxyethanol is added thereto to prepare a polyethylene glycol citric acid-methoxyethanol solution with a mass concentration of 40-60%; trimethoxymethylsilane is added to the polyethylene glycol citric acid-methoxyethanol solution, and reacted at 35-45° C. for 6-8 h to obtain a polyethylene glycol citric acid-trimethoxymethylsilane solution;
[0010] 2) adding tetraethyl orthosilicate to the polyethylene glycol citric acid-trimethoxymethylsilane solution obtained in step 1) to obtain a colorless solution, then adding calcium 2-methoxyethanol, stirring for 10 to 15 hours, adding water dropwise thereto until the viscosity of the system increases significantly and becomes a paste, transferring the obtained mixture to a Teflon mold, gelling at 25 to 30° C. for 24 to 36 hours, then transferring to an oven, and drying at 50 to 65° C. for 5 to 8 days to obtain a bioglass-polycitric acid composite;
[0011] 3) Soaking the bioglass-polycitric acid complex prepared in step 2) in distilled water for 48 to 72 hours, filtering it 2 to 3 times with a 0.22 μm membrane, and drying the filtrate at 45° C. to obtain bioglass-polycitric acid derived luminescent carbon dots.
[0012] The molar ratio of polyethylene glycol, citric acid and trimethoxymethylsilane in step 1) is 1:0.8-1.2:0.7-0.9.
[0013] The mass ratio of the total mass of tetraethyl orthosilicate and calcium 2-methoxyethanol added in step 2) to the mass ratio of the polyethylene glycol citric acid-trimethoxymethylsilane solution is 3-6:4-7.
[0014] The molar ratio of tetraethyl orthosilicate to calcium 2-methoxyethoxide in step 2) is 5-8:2-4.
[0015] Preferably, in step 1), the molar ratio of polyethylene glycol, citric acid and trimethoxymethylsilane is 1:1:0.8.
[0016] Preferably, in step 2), the mass ratio of the total mass of tetraethyl orthosilicate and calcium 2-methoxyethanol to the mass ratio of the polyethylene glycol citric acid-trimethoxymethylsilane solution is 5:5.
[0017] Preferably, in step 2), the molar ratio of tetraethyl orthosilicate to calcium 2-methoxyethoxide is 7:3.
[0018] Preferably, the stirring state in step 1) is heated to 140°C.
[0019] Preferably, in step 1), a polyethylene glycol citric acid-methoxyethanol solution with a mass concentration of 50% is prepared.
[0020] The present invention also includes the application of bioglass-polycitrate-derived luminescent carbon dots in cell imaging.
[0021] Compared with the prior art, the present invention has the following advantages:
[0022] The bioglass-polycitric acid-derived luminescent carbon dots of the present invention, and the prepared bioglass-polycitric acid complex, have an osteogenic effect and can promote the osteogenic differentiation of osteogenic precursor cells; and further separate the luminescent carbon dots therefrom, and systematically characterize the structure and fluorescence properties of the obtained carbon dots.
[0023] The bioglass-polycitrate-derived luminescent carbon dots of the present invention have the typical red shift phenomenon of carbon dots, and have the characteristics of low toxicity, good water solubility, high quantum yield and good photostability; at the same time, they can penetrate the cell membrane and locate inside the cell, thereby tracing the cell, and have good application in cell imaging. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is an appearance diagram of the bioglass-polycitric acid composite prepared in Example 3 of the present invention;
[0025] Figure 2 The fluorescence emission of the bioglass-polycitrate complex prepared in Example 3 of the present invention under different excitation lights; wherein (a) is 200-400nm; (b) is 450-480nm; (c) is 500-560nm; Figure 3 Characterization diagram of the bioglass-polycitrate-derived luminescent carbon dots prepared in Example 3 of the present invention; wherein (A) is an infrared spectrum; (B) is an X-ray photoelectron spectrum; (C) is an energy dispersion spectrum;
[0026] Figure 4 (A) is a transmission electron microscope image of the bioglass-polycitric acid-derived luminescent carbon dots prepared in Example 3 of the present invention; (B) is a particle size distribution diagram of the bioglass-polycitric acid-derived luminescent carbon dots prepared in Example 3 of the present invention;
[0027] Figure 5 Spectra of bioglass-polycitrate-derived luminescent carbon dots prepared in Example 3 of the present invention, wherein (A) is a UV-visible absorption spectrum, and the inset is a photograph of CD aqueous solution under visible light (left) and UV light (right); (B) is an excitation-dependent photoluminescence behavior diagram;
[0028] Figure 6 (A) is a graph showing the effect of pH on the photoluminescence intensity of the bioglass-polycitric acid-derived luminescent carbon dots prepared in Example 4 of the present invention; (B) is a graph showing the relationship between the fluorescence intensity and ionic strength of the bioglass-polycitric acid-derived luminescent carbon dots prepared in Example 4 of the present invention in a NaCl aqueous solution (pH=7); (C) is a graph showing the effect of the excitation time on the fluorescence intensity of the bioglass-polycitric acid-derived luminescent carbon dots prepared in Example 4 of the present invention in ultrapure water; (D) is the effect of the storage time on the photoluminescence intensity of the bioglass-polycitric acid-derived luminescent carbon dots prepared in Example 4 of the present invention;
[0029] Figure 7 (A) is a graph showing the effect of different concentrations of luminescent carbon dots on the cell viability of MC3T3-E1 cells after incubation for 24 hours; (B) is a fluorescence image of MC3T3-E1 cells after incubation for 2 hours with the bioglass-polycitrate derived luminescent carbon dots prepared in Example 5 of the present invention. DETAILED DESCRIPTION
[0030] In order to better understand the technical solution of the present invention, the above content of the present invention is further described in detail below through specific implementation methods in the form of embodiments, but this should not be understood as the scope of the above subject matter of the present invention being limited to the following examples. All technologies realized based on the above content of the present invention belong to the scope of the present invention.
[0031] The polyethylene glycol used in the following examples is polyethylene glycol 300.
[0032] Example 1 Under nitrogen protection, 2.24 g of polyethylene glycol and 1.15 g of citric acid were added to a reactor, heated to 130° C. under stirring, reacted for 0.5 h to obtain a polyethylene glycol citric acid prepolymer, cooled to 25° C., and then methoxyethanol was added thereto to prepare a polyethylene glycol citric acid-methoxyethanol solution with a mass concentration of 40%; 0.71 g of trimethoxymethylsilane was added to the polyethylene glycol citric acid-methoxyethanol solution, and the mixture was reacted at 35° C. for 6 h to obtain a polyethylene glycol citric acid-trimethoxymethylsilane solution;
[0033] 3.1 g of tetraethyl orthosilicate was added to a polyethylene glycol citric acid-trimethoxymethylsilane solution to obtain a colorless solution, and then 0.86 g of calcium 2-methoxyethanol was added. After stirring for 10 hours, water was added dropwise until the viscosity of the system increased significantly and became a paste. The obtained mixture was transferred to a Teflon mold, gelled at 25°C for 24 hours, and then transferred to an oven and dried at 50°C for 5 days to obtain a bioglass-polycitric acid composite.
[0034] The prepared bioglass-polycitric acid composite was immersed in distilled water for 48 hours, filtered twice with a 0.22 μm membrane, and the obtained filtrate was dried at 45° C. to obtain bioglass-polycitric acid derived luminescent carbon dots.
[0035] Example 2 Under nitrogen protection, 1.49 g of polyethylene glycol and 1.15 g of citric acid were added to a reactor, heated to 150° C. under stirring, reacted for 1 h to obtain a polyethylene glycol citric acid prepolymer, cooled to 30° C., and then methoxyethanol was added thereto to prepare a polyethylene glycol citric acid-methoxyethanol solution with a mass concentration of 60%; 0.6 g of trimethoxymethylsilane was added to the polyethylene glycol citric acid-methoxyethanol solution, and the mixture was reacted at 45° C. for 8 h to obtain a polyethylene glycol citric acid-trimethoxymethylsilane solution;
[0036] 6.4 g of tetraethyl orthosilicate was added to a polyethylene glycol citric acid-trimethoxymethylsilane solution to obtain a colorless solution, and then 1.15 g of calcium 2-methoxyethanol was added. After stirring for 15 hours, water was added dropwise until the viscosity of the system increased significantly and became a paste. The obtained mixture was transferred to a Teflon mold, gelled at 30° C. for 24 hours, and then transferred to an oven and dried at 50° C. for 8 days to obtain a bioglass-polycitric acid composite.
[0037] The prepared bioglass-polycitric acid composite was immersed in distilled water for 72 hours, filtered three times with a 0.22 μm membrane, and the obtained filtrate was dried at 45° C. to obtain bioglass-polycitric acid derived luminescent carbon dots.
[0038] Example 3 Under nitrogen protection, 2 g of polyethylene glycol and 1.28 g of citric acid were added to a reactor, heated to 140° C. with stirring, reacted for 0.75 h to obtain a polyethylene glycol citric acid prepolymer, cooled to 26° C., and then methoxyethanol was added thereto to prepare a polyethylene glycol citric acid-methoxyethanol solution with a mass concentration of 50%; 0.72 g of trimethoxymethylsilane was added to the polyethylene glycol citric acid-methoxyethanol solution, and the mixture was reacted at 40° C. for 7 h to obtain a polyethylene glycol citric acid-trimethoxymethylsilane solution;
[0039] 5.6 g of tetraethyl orthosilicate was added to the polyethylene glycol citric acid-trimethoxymethylsilane solution to obtain a colorless solution, and then 1.7 g of calcium 2-methoxyethanol was added. After stirring for 12 hours, water was added dropwise until the viscosity of the system increased significantly and became a paste. The obtained mixture was transferred to a Teflon mold, gelled at 28°C for 30 hours, and then transferred to an oven and dried at 55°C for 6 days to obtain a bioglass-polycitric acid composite; its appearance is shown in the figure below. Figure 1 shown by Figure 1It can be seen that the bioglass-polycitric acid composite prepared by the present invention has an orange appearance. The fluorescence emission of the bioglass-polycitric acid composite obtained under different excitation lights is detected, and its spectrum is as follows: Figure 2 As shown by Figure 2 It can be seen that under different excitation light conditions, the complex emits fluorescence of different colors, among which 2(a) emits light blue fluorescence under 200-400nm excitation; 2(b) emits green fluorescence under 450-480nm excitation; 2(c) emits orange-red fluorescence under 500-560nm excitation.
[0040] The prepared bioglass-polycitric acid complex was immersed in distilled water for 58 hours, filtered three times with a 0.22 μm membrane, and the filtrate was dried at 45° C. to obtain bioglass-polycitric acid-derived luminescent carbon dots; the obtained bioglass-polycitric acid-derived luminescent carbon dots were characterized, and the characterization spectrum thereof is shown in FIG. Figure 3 , Figure 4 and Figure 5 As shown. Figure 3 As can be seen from (B), the bioglass-polycitrate-derived luminescent carbon dots prepared in the present invention are mainly composed of carbon and oxygen elements; Figure 4 (A) Transmission electron microscopy shows that the shape of carbon dots is nearly spherical particles with relatively uniform distribution. Figure 4 (B) The particle size diagram shows that the particle size of carbon dots is about 24.2 nm. Figure 5 (B) It can be seen that the emission wavelength of carbon dots gradually increases with the increase of excitation wavelength, that is, there is a "red shift" phenomenon.
[0041] Example 4 Under nitrogen protection, 2 g of polyethylene glycol and 1.4 g of citric acid were added to a reactor, heated to 135° C. with stirring, reacted for 0.6 h to obtain a polyethylene glycol citric acid prepolymer, cooled to 28° C., and then methoxyethanol was added thereto to prepare a polyethylene glycol citric acid-methoxyethanol solution with a mass concentration of 45%; 0.77 g of trimethoxymethylsilane was added to the polyethylene glycol citric acid-methoxyethanol solution, and the mixture was reacted at 38° C. for 6.5 h to obtain a polyethylene glycol citric acid-trimethoxymethylsilane solution;
[0042] 4.1 g of tetraethyl orthosilicate was added to a polyethylene glycol citric acid-trimethoxymethylsilane solution to obtain a colorless solution, and then 1.47 g of calcium 2-methoxyethanol was added. After stirring for 11 hours, water was added dropwise until the viscosity of the system increased significantly and became a paste. The obtained mixture was transferred to a Teflon mold, gelled at 26°C for 34 hours, and then transferred to an oven and dried at 60°C for 7 days to obtain a bioglass-polycitric acid composite.
[0043] The prepared bioglass-polycitric acid composite was immersed in distilled water for 70 hours, filtered three times with a 0.22 μm membrane, and the obtained filtrate was dried at 45° C. to obtain bioglass-polycitric acid derived luminescent carbon dots.
[0044] Example 5 Under nitrogen protection, 2 g of polyethylene glycol and 1.09 g of citric acid were added to a reactor, heated to 145° C. with stirring, reacted for 0.9 h to obtain a polyethylene glycol citric acid prepolymer, cooled to 27° C., and then methoxyethanol was added thereto to prepare a polyethylene glycol citric acid-methoxyethanol solution with a mass concentration of 55%; 0.68 g of trimethoxymethylsilane was added to the polyethylene glycol citric acid-methoxyethanol solution, and the mixture was reacted at 42° C. for 7.5 h to obtain a polyethylene glycol citric acid-trimethoxymethylsilane solution;
[0045] 2.7 g of tetraethyl orthosilicate was added to a polyethylene glycol citric acid-trimethoxymethylsilane solution to obtain a colorless solution, and then 1.52 g of calcium 2-methoxyethanol was added. After stirring for 14 hours, water was added dropwise until the viscosity of the system increased significantly and became a paste. The obtained mixture was transferred to a Teflon mold, gelled at 29° C. for 28 hours, and then transferred to an oven and dried at 55° C. for 6 days to obtain a bioglass-polycitric acid composite.
[0046] The prepared bioglass-polycitric acid composite was immersed in distilled water for 55 hours, filtered twice with a 0.22 μm membrane, and the obtained filtrate was dried at 45° C. to obtain bioglass-polycitric acid derived luminescent carbon dots.
[0047] 1 mg of the bioglass-polycitrate-derived luminescent carbon dots prepared in Example 4 was dissolved in 5 mL of ultrapure water, and then the pH value was adjusted to a range of 2 to 9, and the excitation wavelength was set to 488 nm. The change in the fluorescence intensity of the solution was detected. The effect of pH on the photoluminescence intensity of the luminescent carbon dots is shown in the figure below. Figure 6 (A) As shown; it can be seen from the figure that at different pH values, the fluorescence intensity of the luminescent carbon dots does not change much, indicating that the bioglass-polycitrate-derived luminescent carbon dots prepared by the present invention have good acid and alkali resistance.
[0048] 1 mg of the bioglass-polycitrate-derived luminescent carbon dots prepared in Example 4 was dissolved in 5 mL of ultrapure water, and then 0.1 mL of the water was added to 100 mM, 200 mM, 300 mM, 400 mM and 500 mM NaCl aqueous solutions, respectively. The excitation wavelength was set to 488 nm, and the change in the fluorescence intensity of the solution was detected to observe the relationship between the fluorescence intensity and the ionic strength. The detection results are shown in FIG. Figure 6(B) As shown; it can be seen from the figure that the fluorescence intensity of the luminescent carbon dots does not change much in NaCl aqueous solutions of different concentrations, indicating that the bioglass-polycitrate-derived luminescent carbon dots prepared by the present invention have good salt resistance.
[0049] 1 mg of the bioglass-polycitrate-derived luminescent carbon dots prepared in Example 4 was dissolved in 5 mL of ultrapure water, and the excitation wavelength was set to 488 nm. The effects of setting the excitation time to 600 s, 1200 s, 1800 s, 2400 s, 3000 s and 3600 s at 37° C. on the fluorescence intensity were observed. The detection results are shown in FIG. Figure 6 (C) As shown; it can be seen from the figure that different excitation times have little effect on the fluorescence intensity of the carbon dots, which indicates that the bioglass-polycitrate derived luminescent carbon dots prepared by the present invention have good resistance to photobleaching.
[0050] 1 mg of the bioglass-polycitrate-derived luminescent carbon dots prepared in Example 4 was dissolved in 5 mL of ultrapure water, and the excitation wavelength was set to 488 nm. The fluorescence intensity changes of the carbon dots were observed at 37° C. and stored for 1 to 6 months. The detection results are shown in FIG. Figure 6 (D) As shown; it can be seen from the figure that the fluorescence intensity of the carbon dots remains basically unchanged, indicating that the bioglass-polycitrate-derived luminescent carbon dots prepared by the present invention have photostability for long-term storage.
[0051] In order to detect the cytotoxicity of the bioglass-polycitrate-derived luminescent carbon dots prepared in the present invention, MC3T3-E1 cells (100 μL) were inoculated in a 96-well culture plate containing α-MEM complete medium at a seeding density of 1.0×10 5 After 12 h, the culture medium was replaced with medium containing carbon dots (prepared in Example 5) at different concentrations (0, 10, 20, 50, 100, 200 and 400 μg mL -1 ) of the same volume (200 μL) of culture medium; after 24 hours, 10 μL of MTT (5 mg / mL) was added to each well and incubated for another 4 hours; finally, the culture medium was removed, 100 μL of DMSO was added, and the absorbance of each well was detected. The cytotoxicity calculation formula is as follows:
[0052] Cell viability (%) = A1 / A2 × 100
[0053] Among them, A1 is the absorbance of cells in wells with different concentrations of carbon dot culture medium, and A2 is the absorbance of cells in wells without carbon dot culture medium. The test results are as follows Figure 7 As shown in (A), it can be seen from the figure that the carbon dots prepared by the present invention have little effect on the absorbance of cells, indicating that the cytotoxicity of the bioglass-polycitrate-derived luminescent carbon dots prepared by the present invention is extremely low and the cell compatibility is good.
[0054] In order to evaluate the application of the bioglass-polycitrate derived luminescent carbon dots prepared by the present invention in biomarkers, MC3T3-E1 cells were cultured in α-MEM complete culture medium containing 10% fetal bovine serum, 100 μg / mL penicillin and 100 μg / mL streptomycin in an environment of 5% CO2 and 37°C. When the cell concentration reached 5×10 5 After the cells reached 400 μg / mL, they were inoculated on the well plate and cultured for 24 h. Then, the cells were incubated with 100 μg / mL carbon dot solution (prepared in Example 5) for 2 h, and then washed three times with phosphate buffered saline (PBS). Finally, a confocal fluorescence microscope (2x objective) was used to take pictures and record them under 488 nm excitation light. The results are shown in Figure 2. Figure 7 As shown in (B), it can be seen from the figure that the carbon dots can enter the cell through the cell membrane and are evenly and regularly distributed in the cytoplasm. These results show that the bioglass-polycitrate-derived luminescent carbon dots prepared by the present invention have great potential in cell imaging, drug delivery and bone tissue engineering applications.
[0055] Although the above describes the specific implementation methods of the present invention, it does not limit the scope of protection of the present invention. Based on the technical solution of the present invention, various modifications or variations that can be made by those skilled in the art without creative work are still within the scope of protection of the present invention.
Claims
1. A method for preparing bioglass-polycitrate-derived luminescent carbon dots, characterized in that: The preparation method is as follows: firstly, a bioglass-polycitrate complex is prepared, and then luminescent carbon dots are separated therefrom; The following steps are involved: 1) Under nitrogen protection, polyethylene glycol and citric acid are added to a reactor, heated to 130-150°C with stirring, reacted for 0.5-1h to obtain a polyethylene glycol citric acid prepolymer, cooled to 25-30°C, and then methoxyethanol is added thereto to prepare a polyethylene glycol citric acid-methoxyethanol solution with a mass concentration of 40-60%; trimethoxymethylsilane is added to the polyethylene glycol citric acid-methoxyethanol solution, and reacted at 35-45°C for 6-8h to obtain a polyethylene glycol citric acid-trimethoxymethylsilane solution; 2) Tetraethyl orthosilicate is added to the polyethylene glycol citric acid-trimethoxymethylsilane solution prepared in step 1) to obtain a colorless solution, and then calcium 2-methoxyethanol is added. After stirring for 10 to 15 hours, water is added dropwise until the viscosity of the system increases significantly and becomes a paste. The obtained mixture is transferred to a Teflon mold, gelled at 25 to 30° C. for 24 to 36 hours, and then transferred to an oven and dried at 50 to 65° C. for 5 to 8 days to obtain a bioglass-polycitric acid composite; 3) Soaking the bioglass-polycitric acid complex prepared in step 2) in distilled water for 48-72 hours, filtering it 2-3 times with a 0.22 μm membrane, and drying the filtrate at 45° C. to obtain bioglass-polycitric acid-derived luminescent carbon dots.
2. The method for preparing bioglass-polycitrate-derived luminescent carbon dots according to claim 1, characterized in that: The molar ratio of polyethylene glycol, citric acid and trimethoxymethylsilane in step 1) is 1:0.8~1.2:0.7~0.
9.
3. The method for preparing bioglass-polycitrate-derived luminescent carbon dots according to claim 1, characterized in that: The mass ratio of the total mass of tetraethyl orthosilicate and calcium 2-methoxyethanol added in step 2) to the mass ratio of the polyethylene glycol citric acid-trimethoxymethylsilane solution is 3-6:4-7.
4. The method for preparing bioglass-polycitrate-derived luminescent carbon dots according to claim 1, characterized in that: The molar ratio of tetraethyl orthosilicate to calcium 2-methoxyethoxide in step 2) is 5-8:2-4.
5. The method for preparing bioglass-polycitrate-derived luminescent carbon dots according to claim 1, characterized in that: The molar ratio of polyethylene glycol, citric acid and trimethoxymethylsilane in step 1) is 1:1:0.
8.
6. The method for preparing bioglass-polycitrate-derived luminescent carbon dots according to claim 1, characterized in that: The mass ratio of the total mass of tetraethyl orthosilicate and calcium 2-methoxyethoxide added in step 2) to the polyethylene glycol citric acid-trimethoxymethylsilane solution is 5:5; the molar ratio of tetraethyl orthosilicate and calcium 2-methoxyethoxide in step 2) is 7:
3.
7. The method for preparing bioglass-polycitrate-derived luminescent carbon dots according to claim 1, characterized in that: The mixture is heated to 140° C. under stirring as described in step 1).
8. The method for preparing bioglass-polycitrate-derived luminescent carbon dots according to claim 1, characterized in that: In step 1), a polyethylene glycol citric acid-methoxyethanol solution with a mass concentration of 50% is prepared.
9. Application of the bioglass-polycitrate-derived luminescent carbon dots obtained by the preparation method of claim 1 in cell imaging.
Citation Information
Patent Citations
KR20220036544A